2011
DOI: 10.1017/s109285291200034x
|View full text |Cite
|
Sign up to set email alerts
|

Generic Substitution of Antiepileptics: Need for a Balanced View

Abstract: There is considerable interest and debate concerning the place of generic substitution, especially relating to antiepileptic drugs (AEDs). Sadly, one of the causes of the ongoing debate is confusion, often intentionally fueled by the pharmaceutical industry among health professionals and patients regarding the regulatory determination of bioequivalence. Few understand the correct definition. It is often erroneously stated that to be considered bioequivalent there is an allowed difference in the extent and rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For instance, if the within‐subject variability in drug plasma levels is high, switching to another formulation (innovator or generic), which is usually accompanied by fluctuations in drug plasma levels, may lead to great variations in plasma levels and hence changes in efficacy and safety outcomes. Second, we did not address other factors that may determine effectiveness in clinical practice, such as adherence, which may be particularly relevant in patients with psychiatric disorders 6 , 10 , 21 , 22 . It is possible that distrust of generic drugs makes adherence a problem, which means that it may not be possible to predict equivalence in clinical outcomes on the basis of equivalent pharmacokinetics alone when switching from an innovator to a generic drug.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, if the within‐subject variability in drug plasma levels is high, switching to another formulation (innovator or generic), which is usually accompanied by fluctuations in drug plasma levels, may lead to great variations in plasma levels and hence changes in efficacy and safety outcomes. Second, we did not address other factors that may determine effectiveness in clinical practice, such as adherence, which may be particularly relevant in patients with psychiatric disorders 6 , 10 , 21 , 22 . It is possible that distrust of generic drugs makes adherence a problem, which means that it may not be possible to predict equivalence in clinical outcomes on the basis of equivalent pharmacokinetics alone when switching from an innovator to a generic drug.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most controversial topics in epilepsy management continues to be the generic substitution of antiepileptic drugs (AEDs) and the switching among A-rated generic AED products [1]. The U.S. Food and Drug Administration (FDA) considers A-rated generic medications to be interchangeable and equivalent to their brand name counterparts in safety and efficacy; therefore, generic substitution of many drug classes is a common health care cost-saving practice [2].…”
Section: Introductionmentioning
confidence: 99%
“…This would hold particularly true for patients who are under treatment for chronic medical conditions such as epilepsy, hypertension, diabetes, congestive heart failure, cancer, and others [16][17][18][19][20][21][22] . In principle, relatively small variations in plasma concentrations of critical dose medicines, such as antiepileptic drugs (carbamazepine, phenytoin, gabapentin, lamotrigine, sodium valproate, and others), digoxin, lithium, cyclosporine, warfarin, and others, may cause adverse effects or loss of efficacy.…”
Section: Risks Of Making Non-bioequivalent Drug Products Interchangeablementioning
confidence: 99%
“…However, it is unclear whether there is in fact a significant risk from REF substitution with G drugs in all cases of critical dose medicines. For instance, although there are reports that substitution of anti-epileptic drugs in certain individuals may be problematic leading to breakthrough seizures [16][17][18][19] , a systematic review by Yamada and Welty 23 reached the conclusion that the strongest levels of evidence available suggested that G antiepileptic drug substitution was not problematic. Moreover, a number of studies, systematic reviews and meta-analyses do not lend to notion that switching from brandname to generic medicines might result in loss or worsened control of disease symptoms [24][25][26] .…”
Section: Risks Of Making Non-bioequivalent Drug Products Interchangeablementioning
confidence: 99%